Polaron spin dynamics in high-mobility polymeric semiconductors - Schott, Sam; Chopra, Uday; Lemaur, Vincent; Melnyk, Anton; Olivier, Yoan; Di Pietro, Riccardo; Romanov, Igor; Carey, Remington L.; Jiao, Xuechen; Jellett, Cameron; Little, Mark; Marks, Adam; et al. (Nature Physics, 2019)
Polymeric semiconductors exhibit exceptionally long spin lifetimes, and recently observed micrometre spin diffusion lengths in conjugated polymers demonstrate the potential for organic spintronics devices. Weak spin–orbit and hyperfine interactions lie at the origin of their long spin lifetimes, but the coupling mechanism of a spin to its environment remains elusive. Here, we present a systematic study of polaron spin lifetimes in field-effect transistors with high-mobility conjugated polymers as an active layer. We demonstrate how spin relaxation is governed by the charges’ hopping motion at low temperatures, whereas an Elliott–Yafet-like relaxation due to a transient localization of the carrier wavefunctions is responsible for spin relaxation at high temperatures. In this regime, charge, spin and structural dynamics are intimately related and depend sensitively on the local conformation of polymer backbones and the crystalline packing of the polymer chains.
CRIS-Team Scopus Importer:2023-03-27